Reliability of testing and potential impact on HIV prevention in Nigeria (2006)
Several factors including variability of human immunodeficiency virus (HIV), laboratory facilities, cost and competence of personnel handling the tests are some of the important factors that affect accuracy and reliability of HIV testing in most parts of Africa. Recently investigators in Africa have observed that antibody detection assays based on antigens derived from HIV-1 subtype B show moderate to significantly lower sensitivity for detection of infection by various non-B subtypes. In this study, we evaluated the reliability of two EIA and 12 rapid HIV-1/2 test kits that are commercially available in Nigeria using the Western immunoblotting technique as reference. A panel of 100 sera from Western blot confirmed symptomatic or asymptomatic HIV-1 infected persons and 90 seronegative patients from those referred for testing in our laboratory were used for this study. Each sample was tested with two HIV-1/2 EIA, and 12 HIV-1/2 rapid test kits commercially available at one time or the other for HIV-1/2 testing in Nigeria. Overall, the sensitivity of the two EIA kits were 100% and 91.0% with specificity of 96.7% and 91.1% respectively. The sensitivity of the rapid test kits ranged from 88% to 98.0% with specificity of 92.2% to 100%. Further analysis showed significant variation in the sensitivity and specificity of the same kit based on whether an individual had asymptomatic or symptomatic infection The results of this study highlight the problem of diagnosis of HIV infections in Africa. It shows that the sensitivity of most of the rapid assays shall not be adequate for detection of early infection. The implications of possible misdiagnosis on the various intervention strategies that rely predominantly on correct HIV status of an individual are enormous. Thus, there is an urgent need for review of the current HIV testing assays or algorithms in Nigeria and other parts of Africa.